Frequency-Decrease Effect and Inhibitory Strategies for Capacitor Voltage in MMC-UPFCs Based on Tagging Technology - WANG Chuyang, ZHANG Mengjie, ZHAO Yunlong, ZOU Yuting, ZHANG Li (Dianli jianshe)
[Objective] In this study， we aim to address the submodule capacitor voltage frequency reduction effects and the resulting deterioration in system switching losses and harmonic performance in modular multilevel converter （MMC）-based unified power flow controllers （UPFCs） under low switching frequencies， frequency reduction suppression， and capacitor voltage balancing optimization strategy based on profiling tag technology. [Methods] The proposed strategy first involves constructing a tag system based on the multidimensional data resources of the MMC-UPFC and determining the optimal frequency ratio tag value by combining evaluation tags and optimized parameters. Subsequently， we propose a capacitor voltage-balancing optimization strategy based on tag technology feedback regulation， which selectively activates the voltage-balancing controller when the capacitor voltage imbalance degree exceeds a certain threshold， as determined by the clustering range of the imbalance degree tags. [Results] Simulation results indicate the following： 1） when the frequency ratio is set to 2+1/N， the capacitor voltage imbalance degree stabilizes around 1.6%， whereas it exceeds 3% and continues to rise when the frequency ratio is 2.5； 2） in the capacitor voltage balancing optimization strategy based on tag technology feedback regulation， the bridge arm capacitor voltage imbalance degree can stabilize at 0.7% when the voltage balancing controller is selectively activated， significantly outperforming traditional full-time voltage balancing strategies； 3） at a frequency ratio of RF=2.4， the non-full-time voltage balancing strategy effectively suppresses capacitor voltage fluctuations， reducing the total harmonic distortion （THD） of the AC current from 12.61% under the full-time voltage balancing strategy to 0.11%. [Conclusions] The proposed frequency reduction suppression and capacitor voltage balancing optimization strategy based on profiling tag technology demonstrates excellent performance， addresses the issues of harmonic suppression and capacitor voltage balancing in MMC-UPFC systems under low frequency ratios， and provides theoretical support for the optimized operation of MMC-UPFC systems.